Effect of the Samples’ Surface With Complex Microscopic Geometry on 3 × 3 Mueller Matrix Measurement of Tissue Bulks - Liu, Yi-Rong; Sun, Wei-Zheng; Wu, Jian (Frontiers in Bioengineering and Biotechnology, 2022)
The clinical in-vivo tissue bulks' surface is always coarse, and show a complex microscopic geometry which may affect the visual effect of polarization images and calculation of polarization parameters of the sample. To confirm whether this effect would cause identification difficulties and misjudgments on the target recognition when performed the polarization imaging based on 3×3 Mueller matrix measurement , Cylindrical Type and Slope Type physical models were used to study and analyzed the effect of surface with complex microscopic geometry on the polarization images. Then clinical tumor bulk samples were used to interact with different size of patterns to simulate the different complex microscopic geometry and tested the coarse surface effect on polarization images. Meanwhile, assessment parameters were defined to evaluate and confirm the variation between two polarization images quantitatively. The results showed that the polarization imaging of sample surface with the complex microscopic geometry led to acceptable visual effect and limited quantitatively variation on the value of polarization parameters and assessment parameters, and it caused no identification difficulties on target recognition, indicating that it is feasible to apply the polarization imaging based on 3×3 Mueller matrix measurement on clinical in-vivo tissues with complex microscopic geometry sample surface.